Dimensions and indicators to analyze ethical and copyrights editorial practices in online Latin American scientific journals - Giacometti, Mariano (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
The aim of this paper is to define a set of categories and analysis indicators to evaluate editorial practices regarding copyright management and the compliance with ethical rules by digital open-source scientific journals in Argentina. To achieve this purpose, a survey of national and international rule setting, as well as bibliography, was carried out about this subject. The categories defined center around five main topics: measures favoring information retrieval; opensource access policymaking and explicitation, ethical policymaking; explicitation of plagiarismprevention policies; measures leading to copyright conflict avoidance. Analyzing these categories will enable us to get informed about the current situation regarding editorial practices, the level of abiding and fulfillment of ethical norms and the manner in which copyrightrelated issues are resolved.